Methods of studying the distribution, diversity and abundance of birds in East Africa—some quantitative approaches - Pomeroy, Derek; Dranzoa, Christine (African Journal of Ecology, 1997)
In this paper we compare the use of transect counts with a simpler method of investigating bird diversity and numbers, particularly in terrestrial habitats, both natural and non-natural. Transect Counts (TCs) have long been widely used, whereas Timed Species Counts (TSCs), which estimate relative abundance, are comparatively untried. We find that TSCs give results which are comparable to those from TCs in most respects, except that they can only be used indirectly for estimating population densities, and they give different measures of diversity. However, TSCs generate data on many more species much faster than do TCs and are therefore more cost-effective in most situations. In particular, TSCs are useful for community studies. We show, for example, that in natural habitats bird populations are positively correlated with the amount of woody vegetation, but not with rainfall. Diversity too increases with woody vegetation. Because TSCs are simple, more of them can be made for a given input of time, and hence more distributional data are obtained as an additional benefit.
Keywords: Bird survey methods; Diversity; Kenya